Relationship between small ruminants behaviour and landscape features in Northeast of Portugal - Castro, Marina (2012)
The small ruminant production system in Northeastern Portugal is an extensive activity based on the exploitation of spontaneous resources. The shepherds direct their flocks on daily grazing itineraries over different land use types. These circuits differ hugely throughout the year in organization and duration. The places visited and time spent in each land use type depend on the environmental conditions and needs of the animals. Four flocks (two of goat and two of sheep) were monitored monthly for a year. Each flock was observed for a complete day by an operator using a hand held GPS. Data collected consists of geographical position and type of land use crossed, plus some variables of territory such as slope, altitude and air temperature. Also, animal behaviour was monitored. Behavioural activities (grazing, browsing, resting and walking) and the grazed species were noted every 15 minutes by direct observation (instantly recorded). The corrected frequencies approach was used for the data analysis. The principal aims were to examine the relationship between animal behaviour and land use types, and to check how it changes throughout the year and the time of day (temperature effect and vegetation moisture). Our results suggested a strong relationship between land use types and behavioural activities.